PENGARUH PENGETAHUAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP PERILAKU PEKERJA KONSTRUKSI PADA PROYEK JALAN TOL NUSA DUA-NGURAH RAI–BENOA - Sambira Teja, Made Bayu; Sutarja, IN; Astawa Diputra, Gd (JURNAL SPEKTRAN; Vol 5 No 1 (2017): Vol. 5, No. 1, Januari 2017, 2017)
Abstract : There is incompatibility between the understanding of Occupational Health and Safety (OHS) knowledge with the application of construction workers behavior on the Nusa Dua - Ngurah Rai - Benoa Toll Road Project Pack 3, where the toll road project was built above the sea. There are workers who work with unsafe although they already know how it should work safely, and there are also workers who found himself competent, but need direction and guidance. Therefore, need to know the influence of occupational health and safety knowledge on construction workers behavior seen from several aspects such as definitions and initiation, management systems, mechanisms of personal protective devices, facilities and infrastructure, as well as the risk of OHS. The sampling technique used Non probability sampling with Incidental Sampling method. Data were taken from the assessment of respondents' answers to the questionnaire by workers sampled in the research. Correlation analysis is used to determine the relationship between knowledge of OHS with worker behavior. Regression analysis was used to explain of the knowledge of OHS aspects influence on construction workers behavior together by using the multiple linear regression analysis and partial by using simple linear regression analysis. The research result showed that there is a positive correlation between knowledge of OHS with worker behavior. In term of the OHS knowledge aspects, the use of personal protective devices mechanism aspects and utilization of facilities and infrastructure at work site affect positively / directly proportional and not significant, while aspects understanding of the definition and initiation, understanding of the OHS management system and an understanding of the risks effect Negative / inversely and not significant on the application of construction workers behavior in a secure and safe.
Keywords: OHS Knowledge, Workers Behavior, Toll Road Project